Prevalence and correlates of low-grade systemic inflammation in adult psychiatric inpatients: An electronic health record-based study. (May 2018) - Osimo, Emanuele F.; Cardinal, Rudolf N.; Jones, Peter B.; Khandaker, Golam M.
Highlights: Up-to 40% acute psychiatric inpatients show evidence of low-grade inflammation. Low-grade inflammation is present in all ICD-10 major psychiatric diagnostic groups. Older age increases inflammation, while being married appears to be protective. Inflammation is associated with diagnosis of schizophrenia and bipolar disorder. Inflammation is associated with prescribed antidepressants and medical comorbidity. Abstract: Low-grade inflammation is a risk factor for depression, psychosis and other major psychiatric disorders. It is associated with poor response to antidepressant and antipsychotics, and could potentially be a treatment target. However, there is limited data on the prevalence of low-grade inflammation in major psychiatric disorders, and on the characteristics of patients who show evidence of inflammation. We examined the prevalence of low-grade inflammation and associated socio-demographic and clinical factors in acute psychiatric inpatients. An anonymised search of the electronic patient records of Cambridgeshire and Peterborough NHS Foundation Trust was used to identify patients aged 18–65 years who were hospitalised between 2013 and 2016 (inclusive). We excluded patients on antibiotics or oral steroids, or with missing data. Inflammation was defined using serum C-reactive protein (>3 mg/L) or total white cell count (>9.4 × 10 9 /L) as measured within 14 days of admission. Out of all 599 admissions, the prevalence of inflammation (serum CRP >3 mg/L) in the ICD-10 diagnostic groups of psychotic disorders (F20–29), mood disorders (F30–39), neurotic disorders (F40–48) and personality disorders (F60–69) was 32%, 21%, 22% and 42%, respectively. In multivariable analyses, low-grade inflammation was associated with older age, black ethnicity, being single, self-harm, diagnoses of schizophrenia, bipolar disorder, current treatments with antidepressants, benzodiazepines, and with current treatment for medical comorbidities. A notable proportion of acutely unwell psychiatric patients from all ICD-10 major diagnostic groups show evidence of low-grade inflammation, suggesting inflammation may be relevant for all psychiatric disorders.